Targeted Hepatic Sonography During Clinic Visits for Detection of Fatty Liver in Overweight Children: A Pilot Study. (1st April 2013) - Perito, Emily R.; Tsai, Patrika M.; Hawley, Sarah; Lustig, Robert H.; Feldstein, Vickie A.
Abstract : Objectives: The purpose of this study was to assess the feasibility and utility of targeted hepatic sonography to evaluate for hepatic steatosis during a subspecialty clinic visit. Methods: In this pilot study, we performed targeted hepatic sonography on 25 overweight children aged 7 to 17 years consecutively seen in a pediatric obesity clinic. Long‐axis images of the right lobe of the liver and a split‐screen image of liver and spleen were taken. Images were interpreted in real time by the radiologist and shown to the family. Demographics, clinical measurements, and laboratory parameters were also collected from the specialty clinic visit on the same day. Results: Sonography required a median of 4 minutes during the visit (interquartile range, 3–5 minutes). All consented patients completed the study. The median alanine aminotransferase (ALT) level was 23 U/L in those with no steatosis (n = 14), 26 U/L with mild steatosis (n = 6), and 41 U/L with moderate/marked steatosis (n = 5). Children with ALT levels of 25 to 50 U/L had very variable sonographic measures of hepatic steatosis. When the participants were categorized by the overall degree of fatty liver, hepatic steatosis was significantly associated with the aspartate aminotransferase level ( P = .028), ALT level ( P = .003), and diastolic blood pressure ( P = .05) but did not correlate with age, sex, Latino race, or insulin resistance. Conclusions: Targeted hepatic sonography added information not apparent from routine ALT screening and provided immediate feedback to clinicians and families about the effect of obesity on end organs. This examination could be a feasible, informative addition to screening for children at high risk for nonalcoholic fatty liver disease who are seen in clinics that specialize in obesity.